SELF-REPORTED MOBILE HEALTH APP ENGAGEMENT AND HEALTH-PROMOTING BEHAVIOUR AMONG INDONESIAN ADOLESCENTS: THE MODERATING ROLES OF SOCIAL SUPPORT AND DIGITAL LITERACY - Lia Juniarni; Masdum Ibrahim; Rahmi Imelisa (Jurnal Keperawatan PPNI Jawa Barat, 2026)
Objective: Mobile health applications are increasingly used to support adolescent health promotion, yet the association between adolescents' self-reported engagement with these applications and health-promoting behaviour may depend on psychosocial resources and digital competencies. This study examined the moderating roles of perceived social support and digital literacy in the association between self-reported mobile health app engagement and health-promoting behaviour among Indonesian adolescents. Methods: A quantitative cross-sectional study was conducted among 240 adolescents aged 13-18 years from secondary schools in Bandung City and Bandung Regency, West Java, Indonesia, selected using multistage proportionate stratified random sampling. Data were collected using validated self-report instruments and analysed using descriptive statistics, Pearson correlation, hierarchical multiple regression, and regression-based moderation analysis with demographic covariates controlled. Result: Self-reported mobile health app engagement was positively correlated with health-promoting behaviour (r = .42, p < .001). Perceived social support and digital literacy were significant independent predictors, and both interaction terms were significant, suggesting that the association between self-reported mobile health app engagement and health-promoting behaviour was stronger among adolescents with higher perceived social support and digital literacy. The final model explained 44.9% of the variance in health-promoting behaviour. Consclussion: These findings suggest that adolescent mobile health programmes should integrate digital health literacy development and socially supported engagement strategies to strengthen health promotion outcomes.